Characteristics of the social networks of families living with parental cancer and support provided. Issue 15 (21st April 2019) - Hauken, May Aasebø; Dyregrov, Kari; Senneseth, Mette
Abstract: Objective: To examine the characteristics of the social networks of families living with parental cancer and the kind of social support they provide compared with what the families report having received. Background: Parental cancers are highly distressing for both parents and children. Among other concerns, families report a severe lack of social support. However, we know little about these families' private social networks, nor support provided and received as reported by network members and the family. Methods: Using a descriptive cross‐sectional design, 16 families living with parental cancer and 130 of their network members participated. Healthy parents and network members filled out The Assistance Questionnaire‐Receivers of support (AQR)/The Assistance Questionnaire‐Providers of Support (AQP). Results: Network members were mainly resourceful friends (44%) and family members (42%). Only 1/3 became supporters at diagnosis, and nearly 50% had to be asked. Supporters provided a variety of types of help, especially emotional support. A match between the perception of the healthy parent and that of the network members was found for provided ( p  = 0.211) and received ( p  = 0.741) support. Supporters were satisfied with their provided support, experiencing it as rewarding and associated with few negative aspects. The STROBE checklist for observational studies was followed in reporting the results. Conclusions: The social networks, being mainly family and friends, were able to provide different types of help, especially emotional support. A useful suggestion may be to involve supporters at an earlier stage, providing more practical support. Relevance for clinical practice: Nurses are in a unique position to promote social support for families living with parental cancer by embracing a network focus, by emphasising the importance and potential of social support, by helping families to map their network and by teaching them how to be explicit in their requests for support.